Limbal Relaxing Incision for Treatment of Thermal Corneal Burns - Syed Ali Haider, Qasim Lateef, Irfan Qayyum Malik (Pakistan Journal of Ophthalmology, 2015)
A 60 years old lady, who underwent phaco with lens implantation, received corneal burn from a hot phacoemulsification tip. After two months of surgery her ORBscan showed the corneal burn induced astigmatism of 5.0 D. Her vision was CF unaided and 6/24 with correction. Full thickness limbal relaxing incision was made and after 2 weeks her ORBscan showed very less astigmatism. After 6 weeks her ORBscan corneal topography showed astigmatism of just -0.3 D which was stable until her last follow up at 6 months and her visual acuity which was CF initially improved to 6/12 unaided. She was followed up for a period of six months with ORBscan, uncorrected and best corrected visual acuity. So we concluded that Limbal relaxing incision is a useful technique to reduce the high astigmatism induced by thermal corneal burns and to improve the visual outcome. Key words: Limbal relaxing incision, corneal burn, astigmatism